BENTUK POLA ASUH ORANG TUA DAN IMPLIKASINYA TERHADAP KARAKTER KEMANDIRIAN ANAK - Siti Nur Amanah Amanah (IAIC (Institut Agama Islam Cirebon), 2020)
Children parenting according to Hurlock, Hardy & Heyes are divided into threetypes, namely: (1) Authoritarian parenting (which tends to require children to obey allparents' decisions), (2) Democratic parenting (which tends to encourage children toopen, but responsible and independent), (3) Permissive parenting (which tends to givefull freedom to children to do). From that three types of parenting, democraticparenting is more supportive of children's development, especially in terms ofindependence and responsibility.